Functional movement development for athletic performance - Webb, A. (Journal of Australian Strength and Conditioning, 2016)
The purpose of this study was to review the factors influencing functional movement development (FMD) and demonstrate how FMD may enhance movement for sports performance. The review also identifies the increasing trend of movement screening protocols, which may lead to decreased injury and subsequent greater efficiency in movement for sports performance. Recent research shows that there is a mixed opinion of the capability for movement screenings to provide accurate predictive information for both injury status and performance enhancement. Due to the differing nature of the multiple studies, there is no strong `conclusive` evidence to date that a movement screening is capable of accurately predicting injury and that athletes with high movement screen scores will have greater performance improvement, however numerous studies have shown evidence of predictive capabilities with differing degrees of accuracy. There is reason for implementing a movement screening model, as it may ascertain a benchmark for functional capability with which a strength and conditioning coach can then provide further exercise prescription over time and improve the likelihood of minimizing athletic injury and enhancing performance status longitudinally. A research review for strength and conditioning coaches is provided outlining a number of recommendations for implementation into strength and conditioning exercise prescription. Examples of exercise prescriptions are provided in both photo and video formats demonstrating principles discussed in the literature.